Investigating the Role of Electronic Banking Services in Improving Social Welfare (Customers of Melli Bank of Iran In Ahwaz Metropolis) (International Journal of Applied Research in Management and Economics, 2018)
The development of IT and e-business has affected all industries and the emergence of e-commerce in banks has been more than all. Nowadays, banks are trying to increase satisfaction and trust customers by delivering Valuable and quality service, in order to increase their customer loyalty and, consequently, their willingness to re-purchase. Accordingly, in this research with an applied approach, we examine the role of e-banking in increasing social welfare. The statistical Society includes customers and users of the Melli Bank of Iran e-banking Services at Ahwaz metropolis. Due to the unlimited size of the statistical Society and using the Morgan table, a statistical sample Volume, 384 people were determined, needed information using an available sampling method and a standard questionnaire was collected. The validity and reliability of the questionnaire indicated the of questions and research variables are reliable. To analyze the data, method analysis of variance was done as partial squares or PLS, and Smart PLS3 software was used for this purpose. The results show that e-banking services at the Melli Bank of Iran have a positive and significant effect on increasing the social welfare of customers and users of these services.